2011
DOI: 10.1002/ijc.27342
|View full text |Cite
|
Sign up to set email alerts
|

Elevated circulating sclerostin correlates with advanced disease features and abnormal bone remodeling in symptomatic myeloma: Reduction post‐bortezomib monotherapy

Abstract: Sclerostin is a Wingless and Int-1 inhibitor, which is produced by osteocytes and inhibits osteoblast-driven bone formation. Sclerostin is implicated in the pathogenesis of bone loss in metabolic bone disorders but there is no information for its effect on multiple myeloma (MM)-related osteolytic disease. We evaluated circulating sclerostin in 157 newly diagnosed patients with symptomatic myeloma, in 25 with relapsed myeloma who received bortezomib monotherapy, in 21 patients with monoclonal gammopathy of unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(101 citation statements)
references
References 20 publications
1
99
0
Order By: Relevance
“…However, recent data show that circulating sclerostin levels are higher in MM patients as compared with MGUS and healthy controls with highest levels in those patients with advanced disease including bone fractures. 47 We can suppose that these high sclerostin levels could be derived directly from MM cells rather than from osteocytes because it has been reported that MM cells overexpress sclerostin. 48 Nevertheless, we cannot exclude that apoptotic osteocytes contribute to the increased sclerostin levels in MM patients because it has been reported that pro-apototic factors may induce sclerostin expression by osteocytes and OBs.…”
Section: Discussionmentioning
confidence: 98%
“…However, recent data show that circulating sclerostin levels are higher in MM patients as compared with MGUS and healthy controls with highest levels in those patients with advanced disease including bone fractures. 47 We can suppose that these high sclerostin levels could be derived directly from MM cells rather than from osteocytes because it has been reported that MM cells overexpress sclerostin. 48 Nevertheless, we cannot exclude that apoptotic osteocytes contribute to the increased sclerostin levels in MM patients because it has been reported that pro-apototic factors may induce sclerostin expression by osteocytes and OBs.…”
Section: Discussionmentioning
confidence: 98%
“…Additional studies have revealed that myeloma cells also suppress osteoblasts by secreting sclerostin 91 . A positive correlation between severity of bone disease and circulating levels of serum sclerostin suggests multiple myeloma cells utilize sclerostin in the formation of osteolytic lesions 92 .…”
Section: Metastatic Bone Cancer and Cancer-induced Bone Lossmentioning
confidence: 99%
“…87 Anti-DKK1 does not have direct anti-tumor effects, although anti-DKK1 may suppress tumor growth via its effects on osteoblast differentiation. 88,89 Sclerostin is an inhibitor of the downstream Wnt signaling pathway and is produced by osteocytes to inhibit osteoblast differentiation. Antibodies to sclerostin are potent inducers of bone formation in preclinical models.…”
Section: Dickkopf1mentioning
confidence: 99%
“…90 Sclerostin levels correlate with the extent of bone destruction in patient with myeloma. 89 Giuliani and coworkers recently reported that osteocyte apoptosis occurs in myeloma, and apoptotic osteocytes may release both RANKL and sclerostin. 91 Transforming growth factor-␤ .…”
Section: Dickkopf1mentioning
confidence: 99%